War makes me sad = (Malungkot ako kapag may digmaan) - Ordinario, Mary Ann (ABC Educational Development Center, 2007)
"The war in Mindanao between Muslims and Christians is very real and this is how an innocent child experiences it. Feel their fear, tragedy, suffering, and their longing for peace."--Pumplepie Books & Happiness.